Evidence for involvement of Saccharomyces cerevisiae protein kinase C in glucose induction of HXT genes and derepression of SUC2 - Brandão, R. L.; Etchebehere, L.; Queiroz, C. C.; Trópia, M. J.; Ernandes, J. R. [UNESP]; Gonçalves, T.; Loureiro-Dias, M. C.; Winderickx, J.; Thevelein, J. M.; Leiper, F. C.; Carling, D.; Castro, I. M. (Elsevier, 2002)
The PKC1 gene in the yeast Saccharomyces cerevisiae encodes protein kinase C that is known to control a mitogen-activated protein (MAP) kinase cascade consisting of Bck1, Mkk1 and Mkk2, and Mpk1. This cascade affects the cell wall integrity but the phenotype of Pkc1 mutants suggests additional targets which have not yet been identified. We show that a pkc1Δ mutant, as opposed to mutants in the MAP kinase cascade, displays two major defects in the control of carbon metabolism. It shows a delay in the initiation of fermentation upon addition of glucose and a defect in derepression of SUC2 gene after exhaustion of glucose from the medium. After addition of glucose the production of both ethanol and glycerol started very slowly. The V max of glucose transport dropped considerably and Northern blot analysis showed that induction of the HXT1, HXT2 and HXT4 genes was strongly reduced. Growth of the pkc1Δ mutant was absent on glycerol and poor on galactose and raffinose. Oxygen uptake was barely present. Derepression of invertase activity and SUC2 transcription upon transfer of cells from glucose to raffinose was deficient in the pkc1Δ mutant as opposed to the wild-type. Our results suggest an involvement of Pkc1p in the control of carbon metabolism which is not shared by the downstream MAP kinase cascade. © 2002 Federation of European Microbiological Societies. Published by Elsevier Science B.V. All rights reserved.
Keywords: Protein kinase C; Saccharomyces cerevisiae; Signal transduction; alcohol; fungal enzyme; galactose; glucose; glycerol; mitogen activated protein kinase; protein kinase C; raffinose; alcohol production; carbon metabolism; cell transfer; controlled study; downstream processing; enzyme activity; fermentation; fungal gene; fungus growth; fungus mutant; gene hxt; gene induction; gene repression; gene suc2; genetic code; genetic transcription; glucose transport; nonhuman; Northern blotting; oxygen consumption; wild type; Saccharomyces